2006
DOI: 10.1158/1078-0432.ccr-06-0834
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Is Highly Expressed in Pancreatic Cancer and Is Associated With Shorter Overall Survival Times

Abstract: Purpose: Peroxisome proliferator-activated receptor γ (PPARγ) is a ligand-activated transcription factor that has been implicated in carcinogenesis and progression of various solid tumors, including pancreatic carcinoma. We aimed to clarify the expression patterns of PPARγ in pancreatic ductal carcinomas and to correlate these to clinicopathologic variables, including patient survival. Experimental Design: Array-based expression profiling of 19 microdissected carcinomas and 14 normal ductal epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 48 publications
2
45
1
Order By: Relevance
“…Moreover, in human pancreatic and ovarian cancers expression profiles indicate a strong overexpression of PPARc that positively correlate with higher pT stages and higher tumor grade. 29,30 Interestingly, our experiments showed that in Tg(HBV)CreKOc mice TZD administration inhibits tumor formation with a potency significantly higher than in parental and control mice. Moreover, PPARc ectopic expression in PPARc-deficient hepatocytes reduced the antiproliferative effect of TZD (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, in human pancreatic and ovarian cancers expression profiles indicate a strong overexpression of PPARc that positively correlate with higher pT stages and higher tumor grade. 29,30 Interestingly, our experiments showed that in Tg(HBV)CreKOc mice TZD administration inhibits tumor formation with a potency significantly higher than in parental and control mice. Moreover, PPARc ectopic expression in PPARc-deficient hepatocytes reduced the antiproliferative effect of TZD (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 76%
“…PPARγ plays an important role in insulin sensitization and differentiation of adipocytes, monocytes and macrophages [5] . Activation of PPARγ can also induce growth inhibition in human prostate cancer cells, colon cancer cells, gastric cancer cells [10] , pancreatic cancer cells [12][13][14][15][16][17] and liposarcoma cells [18] . The expression of PPARγ and its role in human pancreatic carcinoma have not been fully elucidated.…”
Section: Figure 8 Immunohistochemical Analysis Of Microvessel Densitymentioning
confidence: 99%
“…It has been shown that PPARγ gene expression is observed in a variety of tissues, including adipose tissue and tumor tissue. Some in vitro studies have recently reported that PPARγ activation has inhibitory effects on the growth of pancreatic carcinoma cells [13][14][15] , probably due to its up-regulation of cellular apoptosis and its down-regulation of tumor invasion [16][17][18] . However, little attention has previously been paid to PPARγ action on the growth of pancreatic carcinoma in vivo, especially its regulation action on tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ and its ligands have thus become one of the main focuses of basic tumor research. Currently, the results of studies on PPARγ in pancreatic cancer have demonstrated that PPARγ is highly expressed in pancreatic tumor tissues (17) and PPARγ activation by ligands inhibits the growth and arrests the cell cycle of human pancreatic cancer cells at the G1 phase through various pathways (5,(18)(19)(20). Itami et al (20) found that overexpression of PPARγ in the pancreatic cancer cell line KMP-3 led to lipid accumulation, while treatment with TGZ increased the level of p27Kip1 and thereby arrested the cell cycle at G1 phase.…”
Section: Discussionmentioning
confidence: 99%